Development of trigonometry learning kit with a STEM approach to improve problem solving skills and learning achievement - Aulia Nur Arivina; Jailani Jailani (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2020)
This study aimed to produce the trigonometry learning kit for tenth-grade high school students using the STEM (Science, Technology, Engineering, and Mathematics) approach properly. This study was development research using the ADDIE model, which consisted of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. This study's subjects were tenth-grade high school students (n = 32) in Semarang, Indonesia. Data collection was carried out through questionnaires and tests. To assess the learning kit's validity, we used a questionnaire with the expert (mathematics education lecturers) as data sources. To assess the learning kit's practicality, we used the questionnaire (with teacher and student as data sources) and observation sheets. We used a test to assess the learning kit's effectiveness in terms of problem-solving skills and learning achievement. This development resulted in the trigonometry learning kit in the form of lesson plans or Rencana Pelaksanaan Pembelajaran (RPP) and worksheets or Lembar Kerja Peserta Didik (LKPD) using the STEM approach properly (meet the criteria of being valid, practical, and effective). The learning kit characteristics were: facilitating problem-solving skills and learning achievement, using problems related to Science, Technology, Engineering, and Mathematics, and organizing based on the Engineering Design Process (EDP) steps.